2019
DOI: 10.1001/jamanetworkopen.2019.12161
|View full text |Cite
|
Sign up to set email alerts
|

Health System and Beneficiary Costs Associated With Intensive End-of-Life Medical Services

Abstract: Key PointsQuestionWhat is the cost associated with National Quality Forum–identified intensive medical services in the last month of life to beneficiaries and to the health care system?FindingsIn this cohort study of 48 937 patients with cancer enrolled in Medicare and the Veterans Health Administration, those receiving no intensive service had a health system cost of $7660, whereas for the 59% of patients receiving 1 or more intensive services in the last month of life, the cost was $23 612. Expected benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…[3][4][5][6][7][8] Despite best practice guidelines from the American Society of Clinical Oncology and the National Quality Forum that discourage low-value end-of-life care, many patients with metastatic cancer continue to receive aggressive medical interventions throughout their final weeks of life. 9 Patients with advanced cancer often experience a substantial worsening in health during their final months, occasioning inpatient admission and intensive procedures that add to the substantial emotional and financial burden of care during the final stages of illness 4,[10][11][12] ; yet, this intensive inpatient care often does not achieve end-of-life goals for patients and their families or caregivers. 13,14 Furthermore, previous studies have reported higher rates of invasive end-of-life interventions and higher costs incurred among racial or ethnic minority individuals and patients with low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Despite best practice guidelines from the American Society of Clinical Oncology and the National Quality Forum that discourage low-value end-of-life care, many patients with metastatic cancer continue to receive aggressive medical interventions throughout their final weeks of life. 9 Patients with advanced cancer often experience a substantial worsening in health during their final months, occasioning inpatient admission and intensive procedures that add to the substantial emotional and financial burden of care during the final stages of illness 4,[10][11][12] ; yet, this intensive inpatient care often does not achieve end-of-life goals for patients and their families or caregivers. 13,14 Furthermore, previous studies have reported higher rates of invasive end-of-life interventions and higher costs incurred among racial or ethnic minority individuals and patients with low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Obermeyer et al, 12 using an extensive retrospective Medicare database, showed increased costs in the last month of life for patients with poor prognosis cancer. Gidwani-Marszowshi et al, 13 in a 98% male Veterans Administration database, demonstrated that costs with HC were substantially lower and associated with much less aggressive care than NOHC. Chastek et al, 14 in a commercially insured population, reported similar cost findings.…”
Section: Discussionmentioning
confidence: 99%
“…The value of palliative care lies in its ability to raise the quality of life and lower the cost of treatment. In addition, palliative care services also reduce the mean hospitalization duration and cost [ 5 , 7 , 8 ]. It has also been suggested by the American Society of Clinical Oncology and the Institute of Medicine that patients should not receive intensive treatment at the end of their lives [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested by the American Society of Clinical Oncology and the Institute of Medicine that patients should not receive intensive treatment at the end of their lives [ 7 ]. However, many patients with late-stage cancer still undergo intensive treatments up to a month before their death [ 8 ]. These increase the healthcare costs not only of patients but also of the medical system.…”
Section: Introductionmentioning
confidence: 99%